2010
DOI: 10.1002/jgt.20477
|View full text |Cite
|
Sign up to set email alerts
|

Cycles of even lengths modulo k

Abstract: Thomassen [9] conjectured that for all natural numbers k > 0 and m, every graph of minimum degree k + 1 contains a cycle of length congruent to 2m modulo k. We prove that this is true for k ≥ 2 if the minimum degree is 2k − 1, which improves the previously known bound of 3k − 2. We also show that Thomassen's conjecture is true for m = 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The conjecture received new attention recently. In particular Liu-Ma [41] settled the case when h is even, and Diwan [24] proved it for m = 2. To date, Sudakov and Verstraëte [52] hold the best known bound for the general case on this problem.…”
Section: Proof Of Lemma 11mentioning
confidence: 97%
“…The conjecture received new attention recently. In particular Liu-Ma [41] settled the case when h is even, and Diwan [24] proved it for m = 2. To date, Sudakov and Verstraëte [52] hold the best known bound for the general case on this problem.…”
Section: Proof Of Lemma 11mentioning
confidence: 97%
“…In 1983, Thomassen [19] conjectured that for all natural numbers m and k, every graph of minimum degree at least k + 1 contains a cycle of length 2m modulo k. Thomassen showed that minimum degree 4m(k + 1) suffices. Cai and Shreve [3] showed that claw-free graphs of minimum degree k + 1 have cycles of all lengths modulo k. Diwan [7] proved that graphs of minimum degree 2k − 1 have cycles of all even lengths modulo k and that Thomassen's conjecture holds for m = 2. The currently best known result is by Liu and Ma [12] who verified Thomassen's conjecture if k is even and showed that minimum degree k + 4 suffices if k is odd.…”
Section: Cycle Lengths Modulo Kmentioning
confidence: 99%
“…A theorem of Verstraëte [35] implies that for all k, every graph with average degree at least 8k contains cycles of all even lengths modulo k. For all odd k, a result of Fan [19] shows that minimum degree at least 3k − 2 suffices. Diwan [12] obtained a better bound for Conjecture 1.7 that for every positive integer k, every graph G with minimum degree at least 2k − 1 contains cycles of all even lengths modulo k, and every graph with minimum degree at least k + 1 contains a cycle of length 4 modulo k. For Conjecture 1.8, a recent result of [27] about consecutive odd cycles implies that minimum degree Ω(k) is suffices to ensure the existence of cycles of all lengths modulo k.…”
Section: Cycle Lengths Modulo Kmentioning
confidence: 99%